From Indifference to Resistance. Popular Sectors and the War of Independence in Northern Chile (1817-1823) [de la Indiferencia a la Resistencia. Los Sectores Populares y la Guerra de Independencia en el Norte de Chile (1817-1823)] - Goicovic-Donoso, I (CSIC Consejo Superior de Investigaciones Cientificas, 2014)
Chile s independence movement was led by the Creole elite of landowners and merchants based in Santiago and its surroundings. The subsequent phase of construction of the state and the nation was an expression of their political project. Nonetheless, popular sectors consisting of laborers, craftsmen and farmers, slaves and Indians, remained aloof from this plan and, in the context of the disruption of colonial society, developed strategies of social and political empowerment. Expressions of this were the montoneras (irregular armed forces), banditry and military desertion. This article analyzes the development of these phenomena in northern Chile between 1817 and 1823.